ASSA14-03-20 Cellular repressor of E1A-stimulated genes protects against angiotensin II-induced vascular remodelling via degradation of angiotensin II type 1 receptor. (1st December 2014) - Li, Y; Yan, C; Tian, X; Zhang, Y; Song, H; Zhu, N; Han, Y
Abstract : Background: Cellular repressor of E1A-stimulated genes (CREG), a new cardiovascular homeostasis regulator, has been proposed to reduce the neointimal formation after vascular injury via the maintenance of the quiescent mature vascular smooth muscle cell (VSMC) phenotype. We hypothesised that CREG is a negative regulator of angiotensin (Ang) II-mediated vascular remodelling. Methods: Ten-week-old male heterozygous CREG-deficient (CREG +/- ) mice and their littermate wild-type (WT) mice were used. An osmotic minipump was implanted subcutaneously to infuse a dose of Ang II (1.5 mg/kg · d) or saline (vehicle) for 14 days. Ang II-infused WT mice were then treated with placebo or recombinant human CREG (rhCREG; 300 μg/kg · d). Systolic blood pressure (SBP); extent of vascular remodelling; protein level of collagen type I/III, angiotensin-converting enzyme-2 (ACE2), angiotensin receptor type 1 (AT1R) and Rab7 were evaluated. Primary VSMC culture was performed to assess AT1R and collagen protein expression before and after CREG gene transfection and knockdown. Results: CREG levels are high in vascular media under basal conditions but rapidly decrease in response to Ang II. Ang II infusion for 14 days resulted that levels of SBP, intima medial thickness and vascular remodelling of the aorta and mesenteric artery were significantly greater in CREG +/- mice compared with the WT controls. Vascular gene expression level of CREG was lower in Ang II-treated CREG +/- mice than in WT mice. However, daily treatment of Ang II-infused WT mice with rhCREG blunted the increase of SBP. Ang II-mediated vascular remodelling and expression of collagen type I/III were also suppressed by rhCREG. Moreover, rhCREG treatment inhibited Ang II-mediated up-regulation of AT1R expression and down-regulation of ACE2 expression. Ang II-induced vascular remodelling was inhibited by rhCREG in association with reduced plasma Ang II and increased plasma Ang 1–7 levels. In adult VSMCs, CREG over-expression increased the expression of Rab7 by a regulatory mechanism of ubiquitination. Importantly, Ang II-mediated collagen production and AT1R expression was inhibited by CREG over-expression and augmented by CREG knock-down in a rab7-dependent manner. Conclusions: Elevated Ang II induced hypertension and vascular remodelling, which were exacerbated by CREG deficiency, whereas rhCREG attenuated Ang II-induced adverse vascular remodelling. Hence, CREG is an important negative regulator of Ang II-induced vascular disease and suppresses adverse vascular remodelling.